Transcriptomics modeling of the late-gestation fetal pituitary response to transient hypoxia - Wood, Charles E. (2016)
Background The late-gestation fetal sheep responds to hypoxia with physiological, neuroendocrine, and cellular responses that aid in fetal survival. The response of the fetus to hypoxia represents a coordinated effort to maximize oxygen transfer from the mother and minimize wasteful oxygen consumption by the fetus. While there have been many studies aimed at investigating the coordinated physiological and endocrine responses to hypoxia, and while immunohistochemical or in situ hybridization studies have revealed pathways supporting the endocrine function of the pituitary, there is little known about the coordinated cellular response of the pituitary to the hypoxia. Results Thirty min hypoxia (from 17.0±1.7 to 8.0±0.8 mm Hg, followed by 30 min normoxia) upregulated 595 and downregulated 790 genes in fetal pituitary (123-132 days' gestation; term = 147 days). Network inference of up- and down- regulated genes revealed a high degree of functional relatedness amongst the gene sets. Gene ontology analysis revealed upregulation of cellular metabolic processes (e.g., RNA synthesis, response to estrogens) and downregulation Conclusions The multiple analytical approaches used in this study suggests that the acute response to 30 min of transient hypoxia in the late-gestation fetus results in reduced cellular metabolism and a pattern of gene expression that is consistent with cellular oxygen and ATP starvation. In this early time point, we see a vigorous gene response. But, like the hypothalamus, the transcriptomic response is not consistent with mediation by HIF-1. If HIF-1 is a significant controller of gene expression in the fetal pituitary after hypoxia, it must be at a later time.